ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY OF THE HYDROLYZATE OF GELATIN SKIN FROM Sarda chiliensis chiliensis “bonito” - Tejada Periche, Eder Eduardo (2020)
Fishing activity residues contain high amounts of collagen and gelatin, which with enzymatic hydrolysis processes could manifest some biological activity. The present work aimed to determine the antioxidant and antimicrobial activities of gelatin hydrolysate obtained from Sarda chiliensis chiliensis “bonito” skin collagen. For this, collagen protein fractions were hydrolyzed with alcalase enzime at different conditions of pH, temperature, time and enzyme/ substrate ratio. The in vitro antioxidant activity was evaluated for the fifteen hydrolysates obtained, by 2,2-diphenyl-1-picrylhydracil radical (DPPH) and cationic radical 2,2-azinobis- 3-ethylbenzothiazolin-6-sulfonic (ABTS). The antimicrobial activity was evaluated by disk diffusion and broth microdilution for the minimum inhibitory concentration (MIC). Bonito gelatin hydrolyzates indicated hydrolysis degree above 10 % with a maximum of 33.67 % and showed the IC50 for DPPH between 0.459 and 1.830 mg/mL and for ABTS between 0.749 and 0.200 mg/mL. The lowest and highest TEAC value were 61.76 and 165.38 μmol of trolox/g for hydrolysates H7011 and H7012 respectively. Eight hydrolysates (1.0 mg/mL) presented inhibition halos against Staphylococcus aureus and Bacillus subtilis, and equal or greater MIC than 500 μg/mL. It can be concluded that the obtained hydrolysates showed antioxidant and antimicrobial activities for the experimental model applied.